1977
DOI: 10.1073/pnas.74.7.2607
|View full text |Cite
|
Sign up to set email alerts
|

Excited state lifetimes in cytochromes measured from Raman scattering data: evidence for iron-porphyrin interactions.

Abstract: ABSTRACr Resonance Raman scattering excitation profile data have been obtained on ferrocytochromes c and b5 in the a absorption band region. We observe in cytochrome c that the shape of the excitation profile agrees with the absorption band shape, while in cytochrome b5 it does not. In addition, we observe in cytochrome b5 a linewidth substantially larger than that in cytochrome c. From our data we conclude that the excited state lifetime in cytochrome c is longer than that in cytochrome b5 and that in cytochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 12 publications
2
39
0
Order By: Relevance
“…5 ͑hhc͒ and 6 ͑yc͒. Interestingly, the depolarization of the B 1g bands 10 , 11 , and 13 is systematically larger in the yeast spectrum and exceeds the D 4h value of 0.75. On the contrary, the depolarization ratio of the B 2g band 30 is slightly lower in the yeast spectrum.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…5 ͑hhc͒ and 6 ͑yc͒. Interestingly, the depolarization of the B 1g bands 10 , 11 , and 13 is systematically larger in the yeast spectrum and exceeds the D 4h value of 0.75. On the contrary, the depolarization ratio of the B 2g band 30 is slightly lower in the yeast spectrum.…”
Section: Resultsmentioning
confidence: 88%
“…120 cm −1 splitting of the Q band of ferrocytochrome c at low cryogenic temperatures, which was later found to be mirrored by the resonance Raman excitation profile of the 15 mode. 13 In their investigation of b-type and c-type cytochromes, Wagner and Kassner suggested nearly thirty years ago that the proximal histidine was primarily responsible for lifting the degeneracy of the Q band., 14 Later, Hagihara et al reported Q band splittings in c-type cytochromes with absorption maxima shifting and increasing as temperature was lowered. 15 Collins et al observed significant dispersions of the depolarization ratios of various resonance Raman lines of this cytochrome c species, which were interpreted as indicative to a split between Q x and Q y transitions of the heme group due to electronic perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of myoglobin (and for heme proteins in general), the resonant π-π* Soret excited state is very short lived and population decay takes place within 10-100 fs. [52][53][54][55][56][57] Thus, the long-lived (∼1-2 ps) oscillatory signals that we observe are minimally complicated by optically driven vibrational coherences associated with the Soret excited electronic state.…”
Section: Resultsmentioning
confidence: 99%
“…It was found in the range (3 -100) × 10 −5 sec Friedman, J.M. et al [6] have also studied the excited st tim ointed out excited state of Raman sp o to re…”
Section: Review Of the Literaturementioning
confidence: 99%
“…For the rest of hemoproteins, including the globins, or cytochromes. Some of the researchers [28,29] expected that the weaker the Fe-sixth ligand bond ,the stronger is the internal bond of the sixth ligand e.g. O-O and C-O.…”
Section: Rammentioning
confidence: 99%